PENGELOLAAN PERPUSTAKAAN DI MTsN 3 KOTA PARIAMAN - Ruska, Syofani; Hasnawati, Hasnawati; Anidar, Jum (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2023)
This research is motivated by problems related to library management at MTsN 3 Kota Pariaman which is still not optimal. This can be seen from the process of arranging the books not going well, so that there are several books that are not placed on the shelves according to the type of book and there are still books that are not arranged on the bookshelves, this happens because of the lack of space for bookshelves in the MTsN 3 library Pariaman City. Not only is the book collection lacking, the library facilities at MTsN 3 Kota Pariaman are not yet comfortable, and even the lending service is still manual. The aim of this research is to find out the aspects of library management. The research method used is qualitative with data collection techniques through observation, interviews and documentation. Data analysis techniques in this research are data reduction, data display (data presentation), conclusion drawing/verification (drawing conclusions). Research Results: Aspects of Library Management which are divided into five indicators, namely management of library material collections, inventory, maintenance of library collections, school library equipment and school library administration. First, management of library material collections, managers store collections of library materials using only two methods by purchasing it yourself from the shop with the funds provided, secondly with a gift/donation from class IX students who want to graduate in the form of one novel per student and also a donation from the book shop in the form of an Al-Qur'an. The second inventory activity carried out in the inventory is the examination of library materials, then grouping of collections is carried out by grouping them into fields of study. Then the tasting of library materials is directly provided in the form of stamps on the front and back pages of the book, in recording library materials a book inventory is provided. Third, in maintaining the library collection, cleaning books from dust is carried out every day, repairing damage to books by collecting library materials, arranging books on shelves by arranging books according to class and by subject. The four school library equipment does not have a reading table, there are not enough bookshelves, and there is no computer desk. The five lilibrary administrations record visitors, borrow and return books.